STUDI LITERATUR: ANALISIS KELAYAKAN BAHAN AJAR MENGGUNAKAN GOOGLE SITES PADA KEGIATAN PEMBELAJARAN DI SEKOLAH - Virda, Dimas Ananda; Wahyuni, Eko Sri; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The process of interaction between teachers and students that requires planning to meet the students' understanding is called Learning. This learning process can influence the quality of student learning outcomes, thus necessitating the systematic planning and presentation of materials using educational resources, one of which is by developing teaching materials with a modern approach, such as Google Sites. Google Sites is a free web creation platform that allows users to insert text, images, videos, and more as needed, making it suitable for use in learning activities as a modern interactive teaching resource. The purpose of this research is to conduct a review based on scientific articles discussing the development of teaching materials using Google Sites and the feasibility of its use in learning activities. The literature study method was used in this research by utilizing various scientific articles obtained over the past 5 years. Analysis based on 10 scientific articles shows that Google Sites-based teaching materials are feasible, practical, and effective for use in learning from elementary to secondary school.